Agency problems as a theoretical framework for option remuneration plans: main contributions (Cultura Económica, 2019)
The aim of this essay is to present, very succinctly, the evolution of the theoretical framework of the firm in relation to agency theory and its tensions due to the separation of control by shareholders. In addition, there will be a tour of the main works that linked the problem of the principal-agent, to the existence of a paradigm to deal with the problem of managerial remuneration for option plans.
Keywords: firm theory; information asymmetry; adverse selection; option plans